2015
DOI: 10.1128/jb.00345-15
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vibrio cholerae to the Catecholamine Hormones Epinephrine and Norepinephrine

Abstract: In Escherichia coli or Salmonella enterica, the stress-associated mammalian hormones epinephrine (E) and norepinephrine (NE) trigger a signaling cascade by interacting with the QseC sensor protein. Here we show that Vibrio cholerae, the causative agent of cholera, exhibits a specific response to E and NE. These catecholates (0.1 mM) enhanced the growth and swimming motility of V. cholerae strain O395 on soft agar in a medium containing calf serum, which simulated the environment within the host. During growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 41 publications
1
32
1
1
Order By: Relevance
“…However, this result was in contrast to previous reports that 10 μM NE could induce log-fold changes in A. hydrophila growth (Dong et al, 2016;Kinney et al, 1999). This difference may be attributed to the variation of experimental conditions including transferrin levels, bacterial strains, and inoculum densities in different studies (O'Donnell et al, 2006 (Halang et al, 2015), Aeromonas hydrophilia (Dong et al, 2016),…”
Section: Virulence Enhancement Of Aeromonas Hydrophila By Ne In Vivocontrasting
confidence: 93%
See 1 more Smart Citation
“…However, this result was in contrast to previous reports that 10 μM NE could induce log-fold changes in A. hydrophila growth (Dong et al, 2016;Kinney et al, 1999). This difference may be attributed to the variation of experimental conditions including transferrin levels, bacterial strains, and inoculum densities in different studies (O'Donnell et al, 2006 (Halang et al, 2015), Aeromonas hydrophilia (Dong et al, 2016),…”
Section: Virulence Enhancement Of Aeromonas Hydrophila By Ne In Vivocontrasting
confidence: 93%
“…Based on preliminary tests, we found that NE significantly enhanced the growth of Aeromonas hydrophilia AH196 in the medium with ABS and FBS, and a higher growth stimulation of Aeromonas hydrophilia AH196 was observed in serum‐SAPI medium containing FBS rather than that of ABS (data not shown). The previous studies also have chosen serum‐SAPI medium supplemented FBS as a culture medium to assess the effect of NE on the growth of Vibrio cholerae (Halang et al., ), Aeromonas hydrophilia (Dong et al., ), Campylobacter jejuni (Xu et al., ), and Vibrio parahaemolyticus (Nakano, Takahashi, Sakai, & Nakaya, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several of the strategies used by S. Tm to adapt to host environments are conserved among several organisms such as pathogenic E. coli , Listeria monocytogenes , Brucella abortus , and Staphylococcus aureus . For example, pathogens adapt to the host or regulate virulence by utilizing and/or sensing nitrate ( Spees et al, 2013 ; Winter et al, 2013 ), epi/NE ( Curtis et al, 2014 ; Halang et al, 2015 ; Moreira et al, 2016 ; Rooks et al, 2017 ), ethanolamine ( Maadani et al, 2007 ; Kendall et al, 2012 ; DebRoy et al, 2014 ; Gonyar and Kendall, 2014 ; Mellin et al, 2014 ; Subashchandrabose et al, 2014 ), iron ( Almirón et al, 2001 ; Zimbler et al, 2012 ; Hammer et al, 2013 , 2014 ; Mashruwala et al, 2015 ; Palmer and Skaar, 2016 ), and pH ( Heinzen et al, 1996 ; Sturgill-Koszycki and Swanson, 2000 ; Singh et al, 2008 ; Vandal et al, 2008 ). Additionally, T6SS are widely conserved, particularly within Proteobacteria and Bacteroidetes ( Hood et al, 2017 ), and promote colonization of intestinal pathogens ( Fu et al, 2013 ; Sana et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strains were grown in the presence of 50 g liter Ϫ1 streptomycin at 37°C on mixed amino acids (LB; 10 g liter Ϫ1 tryptone, 5 g liter Ϫ1 yeast extract, 1 g liter Ϫ1 NaCl) or in phosphate-or Tris-buffered M9 minimal medium containing 18.7 mM NH 4 Cl, 0.1 mM CaCl 2 , 0.1 mM MgSO 4 , 40 mg liter Ϫ1 each of methionine, threonine, histidine, and leucine, and 2 mg liter Ϫ1 thiamine, with 0.2% (wt/vol) glucose as a carbon source at pH 7.2. In addition, phosphate-M9 contained 7 g liter Ϫ1 Na 2 HPO 4 , 3 g liter Ϫ1 KH 2 PO 4 , 0.5 g liter Ϫ1 NaCl; Tris-M9 contained 20 mM Tris-HCl, pH 7.2, 1.36 g liter Ϫ1 KH 2 PO 4 , and 2.3 g liter Ϫ1 NaCl (51). It should be noted that 18.7 mM NH 4 Cl is a limiting ammonium concentration for growth of E. coli (29), whereas the amount of phosphate (10 mM KH 2 PO 4 ) in Tris-buffered medium is not limiting for V. cholerae (52).…”
Section: Methodsmentioning
confidence: 99%